2021
DOI: 10.3390/healthcare9081039
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Patterns during COVID-19 Lockdown and Their Relationship with Perceived Immune Fitness and Reported COVID-19 Symptoms

Abstract: Since the outbreak of the 2019 coronavirus (COVID-19) pandemic, lockdown periods have been installed to counteract the spread of the virus. These lockdowns, characterized by social isolation, have been associated with mood changes and increased stress. Individuals have used various strategies to cope with the negative effects of being in lockdown, including increasing the frequency and quantity of alcohol consumption. The aim of this study was to investigate mood before and during lockdown of individuals who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Overall, a significant reduction was found in weekly alcohol consumption and hangover frequency. This is in line with recent research from the Netherlands, also showing a reduction of alcohol intake among young adults [39,40]. With regard to academic performance a similar diverse distribution was seen, including participants with improved or worsened academic functioning.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, a significant reduction was found in weekly alcohol consumption and hangover frequency. This is in line with recent research from the Netherlands, also showing a reduction of alcohol intake among young adults [39,40]. With regard to academic performance a similar diverse distribution was seen, including participants with improved or worsened academic functioning.…”
Section: Discussionsupporting
confidence: 90%
“…during the lockdown reduced alcohol consumption on the heaviest drinking occasion. This observation is consistent with the reduced weekly alcohol consumption of these participants that we reported elsewhere [ 10 ]. While this can be regarded as a positive effect accompanying the lockdown period, it should be noted that this is the mean outcome for the full sample under investigation.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, studies that investigated COVID-19 lockdown effects also presented evidence of changes in weekly alcohol consumption. Specifically, it was shown that about 50% of drinkers either increased or reduced their weekly alcohol intake and the number of drinking days per week [ 10 , 11 , 12 ]. Among drinkers that increased the quantity and/or frequency of weekly alcohol consumption, there was a significant association with greater stress, reduced perceived immune fitness, and increased presence and severity of COVID-19 symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modest effect size is most likely due to the fact that the sample is not homogenous: about one third of the participants (30.7%) did not alter their weekly alcohol consumption during lock-down, whereas 38.3% of drinkers reported a reduction and 31.0% reported an increase in weekly alcohol consumption. A detailed comparison of these groups is presented elsewhere [ 45 ]. Including the relative large number of participants in the analysis that did not alter their drinking behavior has a lowering effect on the observed correlations.…”
Section: Discussionmentioning
confidence: 99%